2023
DOI: 10.3390/cells12010199
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa: Infections, Animal Modeling, and Therapeutics

Abstract: Pseudomonas aeruginosa is an important Gram-negative opportunistic pathogen which causes many severe acute and chronic infections with high morbidity, and mortality rates as high as 40%. What makes P. aeruginosa a particularly challenging pathogen is its high intrinsic and acquired resistance to many of the available antibiotics. In this review, we review the important acute and chronic infections caused by this pathogen. We next discuss various animal models which have been developed to evaluate P. aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 443 publications
0
32
0
2
Order By: Relevance
“…Pseudomonas aeruginosa is a Gram-negative, aerobic, extremely versatile, antibiotic-resistant bacteria and causes infections in the blood, lungs, or other parts after surgery [ 29 ]. Only A. geophilum EO showed activity against Pseudomonas aeruginosa with a MIC value of 200 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a Gram-negative, aerobic, extremely versatile, antibiotic-resistant bacteria and causes infections in the blood, lungs, or other parts after surgery [ 29 ]. Only A. geophilum EO showed activity against Pseudomonas aeruginosa with a MIC value of 200 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Such infections result in significant morbidity, mortality, and healthcare costs, particularly in immunocompromised patients. [ 15 ] Previous studies have attempted to use single antigens of P. aeruginosa strains as vaccine candidates, but none have been licensed for use. [ 3 ] Our approach involved combining nine proteins with antigenic properties, including PcrV, OprF, and OprI, as well as the other proteins selected based on proteomics data.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria were selected due to their propensity to form biofilms, which cause nosocomial infections. 39,40 First, the short-term (3 h) antibacterial efficacy of the QC NPs was assessed against planktonic bacteria using the colony-counting assay. It is found that the QC NPs (5 μg mL −1 ) exhibited remarkable antibacterial properties against both P. aeruginosa and S. aureus, resulting in 6.77-log and 3.42-log reduction, respectively, in the number of bacterial colonies formed (Fig.…”
Section: Antibiofilm Properties Of the Qc Npsmentioning
confidence: 99%